Comparative efficacy of glucagon-like peptide 1 (GLP-1) receptor agonists, pioglitazone and vitamin E for liver histology among patients with nonalcoholic fatty liver disease: systematic review and pilot network meta-analysis of randomized controlled trials. (4th March 2023) - Gu, Yunpeng; Sun, Lei; He, Yining; Yang, Luping; Deng, Chaohua; Zhou, Run; Kong, Tingting; Zhang, Wei; Chen, Yutong; Li, Jie; Shi, Junping
ABSTRACT: Introduction: There is no conclusive evidence comparing the efficacy of glucagon-like peptide 1 (GLP-1) receptor agonists to the other guidelines recommended pharmacotherapy for nonalcoholic fatty liver disease (NAFLD). Therefore, we aim to compare the effects of GLP-1 receptor agonists, pioglitazone and vitamin E in patients with NAFLD. Methods: We searched PubMed, Embase, Web of Science and Cochrane Library up to 11 April 2022. Randomized clinical trials (RCTs) comparing GLP-1 receptor agonists, pioglitazone and vitamin E against placebo or other active controls in patients with NAFLD were included. Results: Nine RCTs including 1482 patients proved eligible. GLP-1 receptor agonists ranked first in steatosis, ballooning necrosis, γ-glutamyl transferase, body weight, body mass index, and triglycerides. Administration of GLP-1 receptor agonists, as compared with placebo, was associated with improvement in liver histology [steatosis (OR = 4.11, 95% CI: 2.83, 5.96), ballooning necrosis (OR = 3.07, 95% CI: 2.14, 4.41), lobular inflammation (OR = 1.86, 95% CI: 1.29, 2.68), fibrosis (OR = 1.52, 95% CI: 1.06, 2.20)]. Conclusions: GLP-1 receptor agonists were as effective as pioglitazone and vitamin E for liver histology among patients with NAFLD. GLP-1 receptor agonists might be considered as an alternative or complementary treatment in the future clinical practice. uf0001